OPTIMIZING THE ROLE OF SiPENA AS AN INTEGRATED DISPUTE RESOLUTION FOR DIGITAL ECONOMY IN INDONESIA - Reka Dewantara; Sukarmi Sukarmi; Nurul Ula Ulya (Universitas Syiah Kuala, 2023)
Start-ups (e-commerce and financial technology) and direct commerce activities for goods and services through social media such as Instagram and Facebook are the prime actors as well as major contributors in the success potential of digital economy. Yet, there is a serious unsolved problem in activities of digital economy, with the non-existence of an integrated mechanism of dispute resolution in all sectors of digital economy. This is also muddled by overlapping regulations, as in the case of Government Regulation 80 of 2019 on Commerce through Electronic Systems (PP PMSE) that delegates compensation to the Trade Ministry, while the Law on Consumer Protection delegates compensation to the BPSK. Further, PP PMSE has not yet accommodated mechanisms of compensation and sanctions. The recommendation of this research is the optimization of the role of SiPENA as an integrated system for the resolution of disputes of digital economy in all sectors in the non-litigation path and its integration with E-Court in the litigation path.